2022
DOI: 10.1111/add.16103
|View full text |Cite
|
Sign up to set email alerts
|

Safety in solitude? Competing risks and drivers of solitary drug use among women who inject drugs and implications for overdose detection

Abstract: Background and aims Solitary drug use (SDU) can amplify risks of fatal overdose. We examined competing risks and drivers of SDU, as well as harm reduction strategies implemented during SDU episodes, among women who inject drugs (WWID). Design A cross‐sectional qualitative study, including telephone and face‐to‐face in‐depth interviews. Setting Baltimore City, MD, USA. Participants Twenty‐seven WWID (mean age = 39 years, 67% white, 74% injected drugs daily) recruited via outreach and street intercept (April–Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…To our knowledge, this protection is not included in any state's 911 Good Samaritan Law. Similar to our findings in the later years of the HIV epidemic [6], in which we identified a host of competing priorities that challenged women's ability to negotiate HIV prevention behavior, Rosen et al's research [7] highlights issues that challenge women's ability to reduce their risk for fatal overdose. Harris et al [14], too, recently found that women worry much more about their personal safety and care-giving responsibilities than the 'inevitability' of overdose.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…To our knowledge, this protection is not included in any state's 911 Good Samaritan Law. Similar to our findings in the later years of the HIV epidemic [6], in which we identified a host of competing priorities that challenged women's ability to negotiate HIV prevention behavior, Rosen et al's research [7] highlights issues that challenge women's ability to reduce their risk for fatal overdose. Harris et al [14], too, recently found that women worry much more about their personal safety and care-giving responsibilities than the 'inevitability' of overdose.…”
supporting
confidence: 82%
“…Rosen et al . [7] bring this scholarship into the current era by addressing the nature of and reasons for solitary drug use (a risk factor for overdose death [8]) among WWUD. They identify three motivations for solitary drug use among women in their sample: (i) the need to alleviate opioid withdrawal symptoms, (ii) a desire to avoid anticipated and experienced substance use stigma and (iii) an attempt to reduce vulnerability to violence while intoxicated.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Solitary drug use is an underaddressed issue. At least 50% of people who use illicit opioids do so when they are alone, which can protect against stigmatization, theft, violence, and external distractions during drug use episodes but can also increase the risk of death . From May 2020 through April 2021, two-thirds of overdose deaths monitored by the Centers for Disease Control and Prevention did not include evidence of a bystander, and only 9% of drug use episodes leading to death were directly witnessed.…”
mentioning
confidence: 99%